Reducing teacher workload: Part 1. (1st October 2019) - Bromley, Matt
Abstract : Excessive and inappropriate workload is a key reason for teachers quitting the profession. In a two-part SecEd Best Practice Focus, Matt Bromley looks at how schools can keep workload in check. In part one, he touches upon the role of leadership, culture, student behaviour, school routines, email and more. He also offers tips to help teachers protect their own wellbeing